Effect of erythropoietin administration on expression of mRNA brain-derived Neutrophic factor, levels of stromal cell-derived Factor-1, and neuron specific enolase in brain injury model SpragueDawley. (October 2021) - Said, Muhammad Fadli; Islam, Andi Asadul; Massi, Muhammad Nasrum; Prihantono,; Hatta, Mochammad; Patellongi, Ilham jaya; Cangara, Husni; Adhimarta, Willy; Nasrullah,; Nasution, Rizha Anshori
Abstract: Background: Traumatic brain injury (TBI) is a complicated condition that is the primary cause of death and disability in children and young adults in developed countries. Various kinds of therapy have been carried out in the management of brain injury, one of which is the administration of erythropoietin (EPO). There are not many studies in Indonesia have proven that EPO administration is effective on parameters such as stromal cell-derived factor 1 (SDF-1), brain-derived neurotrophic factor (BDNF mRNA), and neuron-specific enolase (NSE) in brain injury patients. The purpose of this study was to see how EPO affected BDNF mRNA expression, SDF-1 serum levels, and NSE levels in experimental rats with TBI. Methods: This study was conducted using a rat head injury model. Fifteen rats were randomly assigned to one of three groups: A, B, or C. EPO was administered subcutis with a dose of 30.000 U/kg. Blood samples were taken after brain injury (H0), 12 h (H12), and 24 h (H24) after brain injury. Serum level of SDF-1 and NSE were measured using mRNA BDNF gene expression was measured with Real-Time-PCR, and ELISA. Results: This study found EPO increase BDNF mRNA expression in group C at H-12 (7, 92 ± 0.51 vs 6.45 ± 0.33) compared to group B, and at H-24 (9.20 ± 0.56 vs 7.22 ± 0.19); increase SDF-1 levels in group C at H-12 (7, 56 ± 0, 54) vs 4, 62 ± 0, 58) compared to group B, and at H-24 (11, 32 ± 4, 55 vs 2, 55 ± 0, 70); decrease serum NSE levels in group C at H-12 (17, 25 ± 2, 02 vs 29, 65 ± 2, 33) compare to group B and at H-24 (12, 14 ± 2, 61 vs 37, 31 ± 2, 76); the values are significantly different with p < 0, 05. Conclusion: EPO may have neuroprotective and anti-inflammatory properties in TBI by increasing mRNA BDNF expression and serum SDF-1 levels, and decrease serum NSE levels. Highlights: Traumatic brain injury (TBI) is a major cause of death and lifelong disability. Erythropoietin (EPO) increasing mRNA BDNF expression and serum SDF-1 levels. EPO decrease serum NSE levels. Erythropoietin may have neuroprotective and anti-inflammatory properties.